THE EFFECT OF INSURANCE SYSTEM AND TANGIBLE DEPARTMENT OF FINANCE ACCOUNTING (FA) ON STUDENT LOYALTY WITH MEDIATING VARIABLES OF STUDENT SATISFACTION AT UC MAKASSAR - Widiarti, Ary; Sutanto, J.E; Ardyan, Elia; Antonio, Tony (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This research objectives is to obtain empirical evidence, analyze, and explain the influence of insurance system service quality and tangibles on student loyalty, with student satisfaction as a mediating variable at UC Makassar. The research variables consist of the dependent variable (student loyalty) and the mediating variable (student satisfaction). The sampling method was determinedusing Slovin’s formula and stratified random sampling, resulting in a total of 268 active students from the first to third year at UC Makassar. All research hypotheses were tested using SEM-PLS version 4.0. The findings indicate that the quality of insurance system services has a positive but insignificant relationship with student satisfaction as a mediating variable, and a negative relationship with student loyalty. Conversely, tangibles have a positive and significant effect on student loyalty through student satisfaction as a mediating variable.